Localization of the Epileptogenic Zone by Multimodal Neuroimaging and High-Frequency Oscillation - Li, Xiaonan; Yu, Tao; Ren, Zhiwei; Wang, Xueyuan; Yan, Jiaqing; Chen, Xin; Yan, Xiaoming; Wang, Wei; Xing, Yue; Zhang, Xianchang; Zhang, Herui; Loh, Horace H.; et al. (Frontiers in Human Neuroscience, 2021)
Accurate localization of the epileptogenic zone (EZ) is a key factor to obtain good surgical outcome for refractory epilepsy patients. However, no technique so far can precisely locate the EZ, and there are barely any reports on the combined application of multiple technologies to improve the localization accuracy of the EZ. In this study, we aimed to explore the use of a multimodal method combining PET-MRI, fluid and white matter suppression (FLAWS) - a novel MRI sequence, and high frequency oscillations (HFOs) automated analysis to delineate the epileptogenic zone (EZ). We retrospectively collected fifteen patients with refractory epilepsy who underwent surgery, and used the above three methods to detect abnormal brain areas of all patients. We compared the PET-MRI, FLAWS, and HFOs results with traditional methods to evaluate their diagnostic value. The sensitivities, specificities of locating the EZ, and marking extent removed versus not removed (RatioChann(ev)) of each method were compared with surgical outcome. We also tested the possibility of using different combinations to locate the EZ. The marked areas in every patient established using each method were also compared to determine the correlations among the three methods. The results showed that PET-MRI, FLAWS and HFOs can provide more information about potential epileptic areas than traditional methods. When detecting the EZs, the sensitivities of PET-MRI, FLAWS and HFOs were 68.75%, 53.85% and 87.50%, and the specificities were 80.00%, 33.33% and 100.00%. The RatioChann(ev) of HFO-marked contacts was significantly higher in patients with good outcome than those with poor outcome (p<0.05). When intracranial electrodes covered all the abnormal areas indicated by neuroimaging with the overlapping EZs being completely removed referred to HFO analysis, patients could reach seizure-free (p<0.01). The periphery of the lesion marked by neuroimaging may be epileptic, but not every lesion contributes to seizures. Therefore, approaches in multimodality can detect EZ more accurately, and HFOs analysis may help to define real epileptic areas that may be missed in the neuroimaging results. The implantation of intracranial electrodes guided by non-invasive PET-MRI and FLAWS findings as well as HFOs analysis would be an optimized multimodal approach for locating EZ.